Photoluminescence and electrical properties of SrSmAlO4-doped (Bi0.5Na0.5)0.935Ba0.065TiO3 ferroelectric ceramics. Issue 4 (March 2019) - Liang, Cen; Hao, Jigong; Li, Wei; Du, Juan; Fu, Peng; Hu, Chengchao; Li, Huaiyong; Xu, Zhijun; Chu, Ruiqing
Abstract: (1- x ) (Bi0.5 Na0.5 )0.935 Ba0.065 TiO3 - x SrSmAlO4 (BNBT6.5- x SrSmAlO4 ) lead-free ceramics were prepared through the solid reaction sintering method. The phase structure, electrical and photoluminescence properties of the ceramics were systematically studied. Substitution with SrSmAlO4 induced the transition of coexisting ferroelectric rhombohedral-tetragonal phases to the relaxor pseudocubic phase. This transition was accompanied by the drastic disruption of ferroelectric order and the enhancement of electric-field-induced strain. The BNBT6.5- x SrSmAlO4 ceramics prepared with the dopant concentration of x = 0.012 exhibited a large unipolar strain of 0.41% and a correspondingly large signal piezoelectric d 33 * constant (= Smax / E max ) of 512 pm/V. Moreover, the SrSmAlO4 -modified ceramics prepared in this work exhibited strong orange red emission upon excitation with blue light. The emission intensities of the ceramics were dependent on dopant concentration. The ceramic with the dopant concentration of x = 0.012 demonstrated the strongest emission. It also showed a weak green emission peak at 564 nm that corresponded to the 4 G5/2 → 6 H5/2 transition and two strong red emission peaks at 599 and 646 nm that corresponded to the 4 G5/2 → 6 H7/2 and 4 G5/2 → 6 H9/2 transitions, respectively. These results suggested that the BNBT6.5- x SrSmAlO4 system has multifunctional characteristics and considerable potential applications in novel devices with multiple functions given its excellent integrated luminescence and electrical properties.